Effective leadership and its impact on creating job security (Journal of Humanities and Social Sciences Research, 2023)
This study included effective leadership as an independent variable with itssub-dimensions (subjective skills, intellectual skills, human skills, technicalskills ) The Faculty of Dentistry at Tikrit University has been selected as aresearch community that has adopted the opinions of the senior departments ofthe dean, his assistants, heads of departments, officials of divisions and units,and the number of (52) directors, where the relationship and impact between theindependent variable effective leadership in its four dimensions and thedependent variable job security are tested ، The questionnaire was used as a datacollection tool, where ( 52 ) forms were distributed for the research sample, acomprehensive inventory sample was used , and ( 49) workable forms wererecovered. the main research hypothesis was that there is a correlation and amoral impact between effective leadership and job security، The data wereanalyzed using the spss program, as a number of statistical methods were usedto investigate the validity of the hypothesis, including the correlation coefficient(person) and simple regression analysis, where the results matched the researchhypothesis, it was found that there is a correlation and a moral impact betweeneffective leadership and job security, so several recommendations wereformulated that it is hoped that those concerned will benefit from the currentstudy.